2023
DOI: 10.3390/jof9111102
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Paracoccidioides lutzii: Overview of Changes Triggered by Nitrogen Catabolite Repression

Vanessa Rafaela Milhomem Cruz-Leite,
André Luís Elias Moreira,
Lana O’Hara Souza Silva
et al.

Abstract: Members of the Paracoccidioides complex are the causative agents of Paracoccidioidomycosis (PCM), a human systemic mycosis endemic in Latin America. Upon initial contact with the host, the pathogen needs to uptake micronutrients. Nitrogen is an essential source for biosynthetic pathways. Adaptation to nutritional stress is a key feature of fungi in host tissues. Fungi utilize nitrogen sources through Nitrogen Catabolite Repression (NCR). NCR ensures the scavenging, uptake and catabolism of alternative nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Intrinsic factors involve transcription factors such as MYC, ER, p53, BCAH, and HIF-1a, whereas extrinsic factors include reactive oxygen stress and high-fat diets, among others ( Lewoniewska et al, 2021 ; Mao and Jiang, 2023 ). These factors exert selective pressures on tumor cells, leading to the fact that only those cells that have been transformed through adaptive metabolism can survive and reproduce ( Cruz-Leite et al, 2023 ). In a study by Qianlu Yang et al, the tumour heterogeneity of type A and type B breast cancers was revealed by using metabolomics and transcriptomics techniques.…”
Section: Role Of Mitochondria In Breast Cancermentioning
confidence: 99%
“…Intrinsic factors involve transcription factors such as MYC, ER, p53, BCAH, and HIF-1a, whereas extrinsic factors include reactive oxygen stress and high-fat diets, among others ( Lewoniewska et al, 2021 ; Mao and Jiang, 2023 ). These factors exert selective pressures on tumor cells, leading to the fact that only those cells that have been transformed through adaptive metabolism can survive and reproduce ( Cruz-Leite et al, 2023 ). In a study by Qianlu Yang et al, the tumour heterogeneity of type A and type B breast cancers was revealed by using metabolomics and transcriptomics techniques.…”
Section: Role Of Mitochondria In Breast Cancermentioning
confidence: 99%